(untitled) (Research, Society and Development, 2022)
Objective: to analyze the necessary competencies of nurses in the context of the Adolescent Nursing Consultation in articles published in scientific journals. Methodology: integrative review, carried out in medline, LILACS, BDENF, COLLECT SUS and PAHO IRIS databases. Two searches were performed, using the descriptors: Nurses, Nursing Consultation; Adolescent Health; Adolescent; Primary Care and Nurses. The criteria were, inclusion: complete scientific articles, language Portuguese, published in the last five years (2016 to 2021). And exclusion articles: review articles that did not address the theme. Results: The data of the 9 selected articles are found in two tables, where the level of evidence of them is highlighted. Among the findings is the importance of the teacher’s performance in the development of professional training, because it is in practice that competencies related to the demands of adolescents are obtained. It was possible to identify some competencies of nurses during the adolescent’s consultation: to perform active listening; promote and encourage breastfeeding; bond ing during the consultation; develop care plans and prevention actions. Conclusion: It was evident that for a quality adolescent nursing consultation, it should be invested in the development of competencies throughout the teaching-learning process, starting with graduation and going through the professional life of nurses. Thus, it is essential to implement training actions and guidance to nurses, enabling the development of competencies and the integrality of care in the adolescent’s nursing consultation.